Synthesis, characterization, antimicrobial, cytotoxic, DNA-interaction, molecular docking and DFT studies of novel di- and tri-organotin(IV) carboxylates using 3-(3-nitrophenyl)2-methylpropenoic acid. Issue 14 (18th July 2021) - Tariq, Muhammad; Khan, Rabbia; Hussain, Ajaz; Batool, Atia; Rasool, Faiz; Yar, Muhammad; Ayub, Kurshid; Sirajuddin, Muhammad; Ullah, Faizan; Ali, Saqib; Akhtar, Arusa; Kausar, Samia; et al.
Abstract: One diorganotin(IV) [ n -Bu2 SnL2 ] (1 ) and two triorganotin(IV) carboxylates [ n -Bu3 SnL] (2 ) and [Ph3 SnL] (3 ) [L = 3-(3-nitrophenyl) 2-methylpropenoic acid] were synthesized and characterized by elemental analysis, FT-IR and NMR ( 1 H, 13 C) spectroscopies. The geometry of complexes and binding mode of ligand were worked out through FT-IR and NMR spectroscopies. The ligand coordinate with Sn via carboxylato oxygen in monodentate fashion leading to four coordinated geometries around Sn center. The effectiveness of complexes towards their antimicrobial and cytotoxic potential was evaluated and a significant extent of antimicrobial potential was observed with a few exceptions. Molecular docking studies were performed for these complexes to check their interaction with DNA. Results from this study revealed that these compounds can bind favorably with cisplatin binding site and targeting the major groove of DNA. The complex-DNA interaction study was also performed through UV-Vis spectroscopic technique and viscosity measurement, and the observed experimental results were well matched with theoretical results. Computational vibrational analysis, frontier molecular orbital (FMO), natural bond orbitals (NBOs), linear and non-linear optical (NLO) properties of ligand and complexes 1 -3 were calculated by density functional theory (DFT) and time-dependent DFT (TDDFT) using CAM-B3LYP/6-31G (d, p) level of theory to evaluate spectroscopic, structural parameters and reactivity patterns. Abstract : UF0001